Political and Legal Perspectives : The Dynamics of Religious Reform in Northern Europe, 1780-1920 - Robbins, Keith (Book collections on Project MUSE., 2010)
Before the last quarter of the eighteenth century there was a generally clear and remarkably uniform pattern of church-state relationships across Europe. In the course of the nineteenth century this firm alliance between political and religious establishments broke down. Religious pluralism developed everywhere, though at different speeds, requiring church and state to reach fresh solutions.This volume Political and Legal Perspectives highlights the impact of broad political change, 'democratization'', on the question of religious reform, in Northern Europe. Competing political parties express.